2021
DOI: 10.1002/jhbp.881
|View full text |Cite
|
Sign up to set email alerts
|

Robotic vs open distal pancreatectomy: A multi‐institutional matched comparison analysis

Abstract: Background Pancreatic surgery is still a challenge even in high‐volume centers. Clinically relevant postoperative pancreatic fistula (CR‐POPF) represents the greatest contributor to major morbidity and mortality, especially following pancreatic distal resection. In this study, we compared robotic distal pancreatectomy (RDP) to open distal pancreatectomy (ODP) in terms of CR‐POPF development and analyzed oncologic efficacy of RDP in the subgroup of patients with pancreatic ductal adenocarcinoma (PDAC). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Subsequent studies including randomized controlled trials would be necessary for further comparisons. Magistri et al 26 reported that RDP is a safe surgical strategy for pancreatic cancer, but there were only 18 cases of RDP in that study. Although studies on the efficacy of laparoscopic radical antegrade modular pancreatosplenectomy have been published, 32,33 there is no research on robotic radical antegrade modular pancreatosplenectomy so far.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Subsequent studies including randomized controlled trials would be necessary for further comparisons. Magistri et al 26 reported that RDP is a safe surgical strategy for pancreatic cancer, but there were only 18 cases of RDP in that study. Although studies on the efficacy of laparoscopic radical antegrade modular pancreatosplenectomy have been published, 32,33 there is no research on robotic radical antegrade modular pancreatosplenectomy so far.…”
Section: Discussionmentioning
confidence: 87%
“…Subsequent studies including randomized controlled trials would be necessary for further comparisons. Magistri et al 26 . reported that RDP is a safe surgical strategy for pancreatic cancer, but there were only 18 cases of RDP in that study.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The special anatomy, complicated vascular variations, and various postoperative complications make pancreatic resection a challenging surgical procedure ( 25 ). As minimally invasive surgery development, LDP and RDP have developed rapidly in recent years ( 28 , 29 ). Previous studies have demonstrated that the LDP has the same safety and efficacy as open surgery ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%